Perhitungan Pajak Penghasilan PPh (Pasal) 21 pada Pegawai Tetap SMA Swasta YPK Medan - Citra Amanda (Akuntansi, 2023)
This study aims to calculate and analyze the Income Tax (PPh) Article 21 for permanent employees at SMA Swasta YPK Medan. PPh Article 21 is a tax levied on income received by employees working at institutions or companies. The research method used is descriptive quantitative with a case study approach, focusing on 10 permanent employees selected as the sample. The data used in the calculation of PPh Article 21 includes monthly gross income, marital status, number of dependents, and allowances received by each employee. The results of the study show that most employees do not have taxable income (PKP) because the total Non-Taxable Income (PTKP) exceeds their net income. The implications of this research highlight the importance of a better understanding of income tax calculations for employees, as well as the need for further monitoring to ensure tax reporting is done accurately and in accordance with the prevailing tax regulations.